Wideband antipodal Vivaldi antenna with enhanced radiation parameters. Issue 15 (1st December 2015) - Dastranj, Aliakbar
Abstract : A modified broadband antipodal Vivaldi antenna for the operating frequency range of 6–18 GHz is presented. In order to eliminate diffraction from sharp ends, the corners of the patches are rounded. As a result, both the gain and directivity are improved. Moreover, one major addition that is done to the antenna is the background plane. The purpose of the backplane, which is made of metal, is to reflect any radiation going in a direction opposite to that of the required. This would then effectively increase the forward radiation, thus contributing to the gain of the antenna structure. In addition to be small in size, the designed antenna exhibits stable radiation patterns over the entire operating bandwidth, relatively high gain of 7–8.4 dB, and low cross‐polarisation. A prototype of the modified antenna is fabricated and verified experimentally. The measured results are in reasonable agreement with the simulation data. Based on the obtained results, the designed antenna can be useful for broadband applications.